A method for testing the printability of ceramic slurry
Through the combined method of plate rheometer and capillary extrusion test, the shortcomings of the printability test of ceramic slurry in the prior art are solved, and the rheological characteristics and liquid phase migration process of ceramic slurry during the extrusion process are realized. Accurate detection improves the accuracy and flexibility of the test.
Patent Information
- Application Number
- CN202111330837.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-11-11
AI Technical Summary
The prior art is difficult to effectively test the printability of ceramic slurries, especially when simulating the extrusion process in the oscillation mode, it is impossible to truly reflect the rheological characteristics of the slurry under shearing, and it is impossible to detect the liquid phase migration process.
A flat plate rheometer was used to conduct linear viscoelastic zone testing, shear performance and structural recovery performance testing, and combined with capillary extrusion testing, simulated the rheological characteristics changes and liquid phase migration process of ceramic slurry during the extrusion process.
This method can more accurately predict the printability of ceramic slurry under different printing conditions, improve the accuracy and flexibility of the test, and detect the impact of the liquid phase migration process on printing properties.
Smart Images

Figure CN116106519B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of three-dimensional printing, and in particular relates to a method for testing the printability of ceramic slurry. Background Art
[0002] Additive manufacturing, also known as 3D printing, is a process of building a target model through computer-aided design (CAD) and controlling a three-dimensional mobile platform to achieve layer-by-layer molding of materials. Compared with other additive molding methods, direct ink writing (DIW) can more conveniently and quickly control the spatial distribution of different material components during molding, and has great application potential in the field of functional gradient material preparation.
[0003] Compared with polymer materials, ceramic materials are more difficult to prepare slurries suitable for straight writing molding. For the drying and debonding process of the green blank, the ceramic slurry requires a higher solid content to avoid deformation and cracking. Increasing the solid content means a higher slurry viscosity, which is usually not conducive to the extrusion of the slurry. For the printing process, if the slurry is too thin, the extruded lines will flow randomly and cannot maintain a fixed shape; if the slurry is too thick, the extruded lines will be rigidly piled together and cannot flow to fill the gaps between them. Therefore, the requirements for ceramic slurries in straight writing molding are complex and demanding. Researchers generally judge whether the slurry is suitable for straight writing molding by observing the morphology of the slurry after extrusion, which is time-consuming and laborious. Therefore, establishing a qualitative and quantitative evaluation strategy that predicts the printability of the slurry has become the key to solving this problem.
[0004] There are relatively few literature reports on the study of ink printability in direct writing molding. Andrew et al. (Soft Matter, 2019, 15: 1444-1456) combined tensile rheology and shear rheology to study the surface tension and rheology of graphene oxide (GO) suspensions of different concentrations. Ultimately, the quantification of "printability" was based on three rheological parameters: storage modulus, solid-liquid transition stress, and flow transition index. However, there are limitations to the multi-step oscillation test: the high strain scan used to simulate the extrusion process cannot reflect the severe shearing effect on the ink during extrusion. M'Barki et al. (Sci. Rep., 2017, 7: 6017) used the time characteristics of boehmite gelation to study the relationship between "printability" and its time-varying rheological behavior. However, the mathematical model they established is only applicable to hydrogel inks with low solid content.
[0005] In addition to considering the changes in the rheological properties of the slurry under shear, the effects of gradient pressure and interaction with the capillary wall on printability cannot be ignored. Similar to traditional extrusion molding, such as shear flow with a yield point and liquid phase migration. The liquid phase migration of the ceramic slurry during extrusion will cause the solvent content of the slurry to change continuously, thereby affecting the density uniformity of the green blank. Capillary rheometers are usually used to measure these influencing factors. Jae et al. (Powder. Technol., 2018, 330: 19-26) used a double-hole capillary rheometer to study the binder composition and tested the rheological properties of lead magnesium niobate-lead zirconate titanate (PMN-PZT) ceramic raw materials for extrusion molding at different shear rates and temperatures. However, this does not reflect the liquid phase migration process that may occur in the raw materials during the extrusion process. Shabnam et al. (Pharm. Dev. Technol., 2013, 18: 112-120) combined a stamping extruder with a universal testing machine to analyze the effects of moisture content, extrusion speed and die length on extrusion pressure, but this required replacing several dies with different aspect ratios and conducting a large number of experiments to obtain complete data.
[0006] At present, there are few reported methods for testing the printability of direct writing slurries, and there is no research on high-solid content ceramic suspensions. The test based on the oscillation mode alone cannot truly reflect the strong shearing effect on the slurry during extrusion. In addition, the rotational rheological test based on the flat plate rheometer cannot obtain the liquid phase migration process that may occur during slurry extrusion. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a method for testing the printability of ceramic slurry, which solves the technical problems that the structural changes experienced when the oscillation mode simulates the slurry extrusion in the existing test are quite different from the actual situation, and the information on the liquid phase migration process that may occur during the slurry extrusion cannot be obtained.
[0008] The present invention provides a method for testing the printability of a ceramic slurry, comprising the following steps:
[0009] Step (1), testing of the linear viscoelastic region of the ceramic slurry: performing amplitude scanning on the ceramic slurry using the stress scanning mode of the flat plate rheometer to obtain the yield point of the ceramic slurry and the limit value of the linear viscoelastic region, wherein the yield point of the ceramic slurry is the stress value corresponding to the turning point where the storage modulus curve changes from a straight line to a curve in the amplitude scanning, and the strain value at the yield point is the limit value of the linear viscoelastic region;
[0010] Step (2), testing the shear properties and structural recovery properties of the ceramic slurry: using a flat plate rheometer to perform three-stage thixotropy tests, namely oscillation, rotation, and oscillation, to simulate the changes in rheological properties during the extrusion of the ceramic slurry; wherein the oscillation test uses a strain value less than the linear viscoelastic region limit value obtained in step (1) to control the shear deformation mode, and the rotation test uses a controlled shear rate mode;
[0011] Step (3), testing the continuity and liquid phase migration characteristics of the ceramic slurry: using a capillary extrusion test to obtain a curve showing the relationship between the extrusion pressure and the extrusion displacement of the ceramic slurry during the extrusion process.
[0012] Preferably, the stress scanning range of the amplitude scanning in step (1) is 0-10000 Pa, and the frequency is 1-5 Hz.
[0013] Preferably, the oscillation frequency of the oscillation test in step (2) is 1-5 Hz, and the oscillation time is 30-300 s; the frequency of the rotation test in step (2) is 1-5 Hz, the time is 30-60 s, and the shear rate range is 50-150 s -1 .
[0014] Preferably, in the structural recovery property test described in step (2), the ceramic slurry having a storage modulus value between 2300-6000 Pa and being able to be substantially completely recovered has good printability.
[0015] Preferably, in the capillary extrusion test described in step (3), the test device used includes a piston, a barrel, a rubber stopper, a capillary and a supporting structure; the piston moves vertically downward at a constant speed of 0.3-3 mm / min under the drive of a universal testing machine to extrude the slurry in the barrel, and the piston movement speed is determined according to the volume flow rate of the ceramic slurry. The relationship between the pressure and displacement of the piston is recorded by the universal testing machine, and the relevant information of the slurry liquid phase migration is obtained through the relationship between the displacement and the pressure curve; the fluctuation of the pressure curve reflects the stability of the slurry during extrusion, and the pressure reflects the difficulty of slurry extrusion.
[0016] Preferably, in the capillary extrusion test described in step (3), when there is an obvious peak in the extrusion pressure and extrusion displacement curve during the ceramic slurry extrusion process, and the extrusion pressure does not increase significantly with the increase of displacement, it indicates that the ceramic slurry has good printability.
[0017] The present invention provides a method for testing the printability of a ceramic slurry, comprising the following steps:
[0018] The first step is to perform amplitude scanning on the slurry using the controlled stress scanning mode of the plate rheometer, and obtain the yield point and the limit of the linear viscoelastic region of the ceramic slurry through amplitude scanning. The yield point of the slurry refers to the stress value corresponding to the turning point where the storage modulus curve changes from a straight line to a curve in the amplitude scanning, indicating that the slurry begins to soften. The strain value at the yield point is defined as the limit of the linear viscoelastic region, which indicates the range in which the test can be performed without destroying the sample structure, and is used to simulate the static properties of the slurry.
[0019] The second step is to test the structural recovery characteristics of the slurry using a three-stage thixotropy test of oscillation / rotation / oscillation. This test also requires determining the parameters used to simulate the dynamic characteristics of extrusion in the controlled shear rate mode. In the controlled shear rate mode, the maximum shear rate can be obtained by the following equation (1):
[0020]
[0021] Where Q is the volume flow rate of the slurry, and D is the capillary diameter; <v z > is the average flow rate of the slurry flowing through the capillary. Measure the average flow rate <v z >The shear rate of the Newtonian fluid at the capillary wall can be directly calculated. However, general ceramic slurries are non-Newtonian fluids, and their true shear rate is different from the "apparent shear rate" calculated by the above formula. The following equation (2) is called the Weissenberg-Rabinowitsch formula, which is used to calculate the true shear rate of non-Newtonian fluids flowing through the capillary wall:
[0022]
[0023] It can also be written as formula (3):
[0024]
[0025] Where n is the non-Newtonian index of the material, which is equal to The slope of the curve in double logarithmic coordinates. After determining the test parameters through the above formula, the structural recovery characteristics of the slurry can be characterized.
[0026] The third step is to use the capillary extrusion test to record the pressure during the slurry extrusion process, obtain the relationship curve between the extrusion pressure and the extrusion displacement of the slurry during the extrusion process, and analyze the change process of the rheological properties of the slurry. The test device used for the capillary extrusion test is mainly composed of a piston, a barrel, a rubber stopper, a capillary and a support structure. The inner diameter of the barrel and the capillary should be the same as that used in actual printing. The piston moves vertically downward at a constant speed under the drive of the material universal testing machine to squeeze the slurry in the barrel. The piston movement speed is determined according to the volume flow rate of the slurry during the experiment. The relationship between the pressure and displacement of the piston can be recorded by the material universal testing machine. The relevant information of the slurry liquid phase migration can be obtained through the relationship between the displacement and pressure curve. The fluctuation of the pressure curve can reflect the stability of the slurry during extrusion, and its size reflects the difficulty of slurry extrusion. When there is an obvious peak in the extrusion pressure and extrusion displacement curve during the ceramic slurry extrusion process, and the extrusion pressure does not increase significantly with the increase of displacement, it indicates that the ceramic slurry has good printability.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention provides a method for testing the printability of a ceramic slurry. All parameters in the test can be adjusted according to actual application conditions, and can be flexibly used to predict printability under different printing conditions. The method is more consistent with the actual situation and the prediction is more accurate.
[0029] (2) For the first time, capillary extrusion was proposed to determine the printability of ceramic slurry, which can be used as a supplementary test for the printability of ceramic slurry using a plate rheometer. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the amplitude scanning curve and the positions of the yield point and the flow point in the test method of the present invention.
[0031] Figure 2 Schematic diagram of the amplitude scanning curve of the pulp without adding cellulose in Example 1 of the present invention.
[0032] Figure 3 Schematic diagram of amplitude scanning curves of pulps with different cellulose contents in Example 1 of the present invention.
[0033] Figure 4 This is a schematic diagram of the three-stage thixotropic curves of oscillation / rotation / oscillation of pulp with different cellulose contents in Example 1 of the present invention.
[0034] Figure 5 This is a schematic diagram of the fitting curve of the non-Newtonian exponent of the pulp with a cellulose addition amount of 0.50 wt.% in Example 1 of the present invention.
[0035] Figure 6It is a schematic structural diagram of a capillary extrusion die used in the capillary extrusion test in the testing method of the present invention.
[0036] Figure 7 Schematic diagram of the pressure-displacement curve of the slurry in Example 1 of the present invention.
[0037] Figure 8 The morphology of the printed samples of the pulps with different cellulose contents in Example 1 of the present invention.
[0038] Fig. 9 This is a morphology image of a sample after printing of a slurry in which the cellulose addition amount is 0.50 wt.% in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with the accompanying drawings and the following embodiments. It should be understood that the accompanying drawings and the following embodiments are only used to illustrate the present invention rather than to limit the present invention.
[0040] The present invention provides a method for testing the printability of a ceramic slurry, comprising the following steps:
[0041] Step (1), testing of the linear viscoelastic region of the ceramic slurry: using the stress scanning mode of the flat plate rheometer to perform amplitude scanning on the ceramic slurry, obtaining the yield point of the ceramic slurry and the limit of the linear viscoelastic region, wherein the yield point of the ceramic slurry is the stress value corresponding to the turning point where the storage modulus curve changes from a straight line to a curve in the amplitude scanning, and the strain value at the yield point is the limit of the linear viscoelastic region. In one embodiment, the stress scanning range of the amplitude scanning is 0-10000 Pa, and the frequency is 1-5 Hz.
[0042] Step (2), testing of the shear performance and structural recovery performance of the ceramic slurry: using a flat plate rheometer to successively perform three-stage thixotropy tests of oscillation, rotation, and oscillation to simulate the changes in rheological properties during the extrusion of the ceramic slurry; wherein the oscillation test uses a strain value less than the linear viscoelastic zone limit obtained in step (1) to control the shear deformation mode, and the rotation test uses a controlled shear rate mode. In a preferred embodiment, the oscillation test has an oscillation frequency of 1-5 Hz, an oscillation time of 30-300 s, a rotation test has a frequency of 1-5 Hz, a time of 30-60 s, and a shear rate range of 50-150 s -1 In the structural recovery property test of the slurry with good printability, the storage modulus value of the slurry can be basically fully recovered, and the storage modulus value ranges from 2300 to 6000Pa.
[0043] Step (3), testing of the continuity and liquid phase migration characteristics of the ceramic slurry: using a capillary extrusion test, a curve of the relationship between the extrusion pressure and the extrusion displacement of the ceramic slurry during the extrusion process is obtained. This test is based on the pressure-displacement curve and will affect the stability of the flow rate during the extrusion process and the uniformity of the green billet density. The test device used for the capillary extrusion test (such as Figure 6 The material of the present invention is mainly composed of a piston 1, a barrel 2, a rubber stopper 3, a capillary 4, an observation window 5, a support tube 6 and a base 7. The inner diameter of the barrel and the capillary should be the same as that used in actual printing. The piston moves vertically downward at a constant speed of, for example, 0.3-3 mm / min under the drive of a universal testing machine for materials to squeeze the slurry in the barrel. The piston movement speed is determined according to the volume flow rate of the slurry during the experiment. The relationship between the pressure and displacement of the piston is recorded by a universal testing machine for materials, and the relevant information of the migration of the slurry liquid phase is obtained through the relationship between the displacement and the pressure curve. The fluctuation of the pressure curve can reflect the stability of the slurry during extrusion, and its size reflects the difficulty of slurry extrusion. When there is an obvious peak in the extrusion pressure and extrusion displacement curve during the extrusion of the ceramic slurry, and the extrusion pressure does not increase significantly with the increase of displacement, it indicates that the ceramic slurry has good printability.
[0044] The following is an exemplary description of the method for evaluating the printability of the water-based ceramic slurry for direct writing provided by the present invention.
[0045] (1) Preparation of water-based ceramic slurry. Water was used as the dispersion medium, and ceramic powder, dispersant, thickener and other additives were added to obtain a slurry that can be used for direct writing. Another group of ceramic slurries with only ceramic powder and dispersant added were prepared as a control group. Both slurries were degassed and ready for testing.
[0046] (2) Amplitude scanning. The plate rheometer is used to perform amplitude scanning on the slurry to be tested in a controlled stress scanning mode. The stress scanning range is 0 to 10,000 Pa, the frequency is 1 to 5 Hz, and the temperature is 25°C. The yield point of the corresponding ceramic slurry and the limit of the linear viscoelastic region are obtained from the amplitude scanning curve.
[0047] (3) Oscillation / rotation / oscillation three-stage test of the structural recovery characteristics of the slurry. The first stage uses a strain value less than the limit of the linear viscoelastic region to perform an oscillation test in a controlled shear deformation mode, with a frequency of 1 to 5 Hz, a temperature of 25°C, and a time of 30 to 120 s; the second stage uses a rotation test in a controlled shear rate mode, with a frequency of 1 to 5 Hz, a temperature of 25°C, a time of 30 to 60 s, and a shear rate range of 50 to 150 s. -1; The third stage uses the same strain value as the first stage to carry out an oscillation test in a controlled shear deformation mode, with a frequency of 1 to 5 Hz, a temperature of 25°C, and a time of 180 to 300 seconds. From the oscillation / rotation / oscillation three-stage test curve, it can be determined whether the slurry has the shear thinning property, that is, whether it can be continuously extruded and have a certain fluidity after extrusion; and whether it has a structural recovery property (the storage modulus value of the third stage can be restored to a level equivalent to the storage modulus value of the first stage), that is, whether it can maintain a certain shape after deposition.
[0048] (4) Capillary extrusion test. First, add the slurry to be tested into the capillary extrusion die, and then place the piston rod of the die directly below the punch of the universal material mechanical testing machine. The extrusion test is carried out in constant speed mode, and the punch speed is set according to actual needs. The displacement-pressure relationship curve can be obtained through the mechanical sensor of the universal material mechanical testing machine, and the information related to the liquid phase migration during the slurry extrusion process can be obtained based on this curve.
[0049] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples in a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description of this article, and are not limited to the specific values exemplified below.
[0050] Embodiment 1:
[0051] This embodiment is suitable for measuring the printability of a slurry prepared from a mixed powder of aluminum oxide and yttrium oxide.
[0052] (1) Slurry preparation: Using aluminum oxide and yttrium oxide mixed powder raw materials with median particle sizes of 200nm and 1500nm respectively, ultrapure water as solvent, and 0.6wt% ammonium polyacrylate as dispersant, a ceramic slurry with uniform dispersion and solid content of 50vol.% was prepared by ball milling. 0.20wt.%, 0.38wt.%, and 0.50wt.% (relative to the mass of the powder) of hydroxyethyl cellulose were added to three groups of slurries respectively, and another group without cellulose was used as a comparison, and high-speed centrifugation was performed for 10 minutes. The above ceramic slurry was placed in an environment with a temperature of 25°C and a humidity of 85% and left to stand for 2 hours.
[0053] (2) Amplitude scanning: The amplitude scanning of the slurry to be tested was performed using the controlled stress scanning mode of the Haake Viscotester iQ Air plate rheometer produced by Thermo Company of Germany. The stress scanning range was 0-5000 Pa, the frequency was 1 Hz, and the temperature was 25°C. The limits of the linear viscoelastic region of the corresponding ceramic slurry obtained from the amplitude scanning curve were 1.2%, 0.8% and 1.0%, respectively. However, the limits of the linear viscoelastic region could not be obtained from the amplitude scanning curve of the slurry of the control group.
[0054] (3) Structural recovery characteristics test: The structural recovery characteristics of the slurry were tested using a three-stage oscillation / rotation / oscillation test. The first stage used a strain value (0.4%) less than the limit of the linear viscoelastic region to perform an oscillation test in a controlled shear deformation mode, with a frequency of 1 Hz, a temperature of 25°C, and a time of 120 s; the second stage used a rotation test in a controlled shear rate mode, with a frequency of 1 Hz, a temperature of 25°C, a time of 30 s, and a shear rate range of 10 to 85 s. -1 The third section uses the same strain value as the first section to carry out an oscillation test in a controlled shear deformation mode, with a frequency of 1 Hz, a temperature of 25°C, and a time of 300 s.
[0055] (4) Capillary extrusion test: Add the slurry to be tested into Figure 6 The capillary extrusion die is shown in the figure, and then the piston rod of the die is placed directly below the punch of the universal material mechanical testing machine. The extrusion test is carried out in a constant speed mode with a punch speed of 0.36 mm / min. The displacement-pressure relationship curve can be obtained through the mechanical sensor of the universal material mechanical testing machine.
[0056] (5) Printing test: The three groups of slurries were tested for printing on a direct writing printer.
[0057] Figure 1 The schematic diagram of the amplitude scanning curve and the positions of the yield point and flow point. It can be seen from the figure that the yield point of the slurry refers to the stress value (τ) corresponding to the turning point where the storage modulus (G') curve changes from a straight line to a curve. y ); The flow point of the slurry refers to the stress value (τ) corresponding to the intersection of its storage modulus and loss modulus (G") curves. f ).
[0058] Figure 2 This is the amplitude scanning curve of Example 1 without adding cellulose pulp. It can be seen from the figure that the storage modulus and loss modulus of the pulp have more than one intersection point, and there is no obvious solid-liquid transition characteristic. Obviously, it cannot be used for direct writing molding.
[0059] Figure 3The amplitude scanning curves of pulps with different cellulose contents in Example 1 show that there is a transition point between the storage modulus and the loss modulus of the pulp with cellulose added, that is, it has solid-liquid transition characteristics. The yield point of the pulp increases with the increase of cellulose content. The linear viscoelastic zone limits of 0.20wt.%, 0.38wt.% and 0.50wt.% cellulose additions are 1.2%, 0.8% and 1.0% respectively.
[0060] Figure 4 The three-stage thixotropic curve of oscillation / rotation / oscillation of the cellulose content pulp of Example 1. It can be seen from the figure that the storage modulus and loss modulus values of the pulp without cellulose added in the oscillation test are equivalent and there are many intersections. This means that it does not have solid-state characteristics when it is stationary. As the cellulose content increases, the storage modulus of the pulp also increases, and is much larger than the loss modulus value when it is stationary, and has obvious solid-state characteristics. The pulp with added cellulose has shear-thinning characteristics in the second stage of the rotation test, and basically recovers its storage modulus in the third stage of the oscillation test, which illustrates its structural recovery characteristics. However, the storage modulus value of the pulp with only 0.20wt.% cellulose added is relatively low (about 2000Pa), indicating that its solid-state characteristics are not strong enough, which means that it is difficult to maintain a certain shape.
[0061] Figure 6 The self-made capillary extrusion die comprises a piston, a barrel, a rubber stopper, a capillary, an observation window, a support cylinder and a base.
[0062] Figure 7 The pressure-displacement curve of the cellulose content pulp of Example 1. It can be seen from the figure that there is no obvious peak in the pressure-displacement curve of the pulp without cellulose addition, which shows that it will not flow under a pressure greater than a certain pressure, which is consistent with the amplitude scanning result. As the cellulose content increases, the peak pressure of the pulp gradually increases. In addition, the extrusion pressure of the pulp with cellulose addition gradually decreases as the displacement increases. This is caused by the continuous shearing of the pulp under pressure, and it also shows that there is no liquid phase migration process in the pulp.
[0063] Figure 8 The morphology of the blank after printing with the cellulose content slurry of Example 1. It can be seen that the slurry without cellulose is spherical under the action of capillary force after extrusion, and cannot maintain a cylindrical shape, and has no shape retention ability after extrusion. With the increase of cellulose content, the shape retention ability of the slurry is getting better and better. The addition of cellulose in an amount of 0.38wt.% and 0.50wt.% can obtain ceramic slurry with good printability.
[0064] Fig. 9This is the morphology of the sample after printing with the slurry having a cellulose addition amount of 0.50 wt.% in Example 1. The sample size is 32.4×32.4×10 mm, with a clear outline and a complete structure, indicating that the slurry has good printability.
[0065] Without departing from the purpose of the basic characteristics of the present invention, the present invention can be embodied in various forms. Therefore, the embodiments of the present invention are used for illustration rather than limitation. Since the scope of the present invention is limited by the claims rather than the specification, all changes within the scope defined by the claims or within the equivalent scope of the scope defined by the claims should be understood to be included in the claims.
Claims
1. A method for testing the printability of ceramic slurry, characterized in that: The steps include: Step (1), testing the linear viscoelastic region of the ceramic slurry: performing amplitude scanning on the ceramic slurry using the stress scanning mode of the plate rheometer to obtain the yield point of the ceramic slurry and the limit value of the linear viscoelastic region, wherein the yield point of the ceramic slurry is the stress value corresponding to the turning point where the storage modulus curve changes from a straight line to a curve in the amplitude scanning, and the strain value at the yield point is the limit value of the linear viscoelastic region; Step (2), testing the shear properties and structural recovery properties of the ceramic slurry: using a flat plate rheometer to successively perform three stages of thixotropy testing, namely, oscillation, rotation, and oscillation, to simulate the changes in the rheological properties of the ceramic slurry during extrusion; The first oscillation test and the third oscillation test both use a strain value less than the limit value of the linear viscoelastic region obtained in step (1) to perform the test in a controlled shear deformation mode, and the rotation test uses a controlled shear rate mode; Step (3), testing the continuity and liquid phase migration characteristics of the ceramic slurry: using a capillary extrusion test to obtain a curve showing the relationship between the extrusion pressure and the extrusion displacement of the ceramic slurry during the extrusion process; wherein the testing device used comprises a piston, a barrel, a rubber stopper, a capillary and a supporting structure; the piston moves vertically downward at a constant speed of 0.3-3 mm / min under the drive of a universal testing machine to extrude the slurry in the barrel, the piston movement speed is determined according to the volume flow rate of the ceramic slurry, the relationship between the pressure and the displacement of the piston is recorded by the universal testing machine, and the relevant information on the liquid phase migration of the slurry is obtained through the relationship between the displacement and the pressure curve; the fluctuation of the pressure curve reflects the stability of the slurry during extrusion, and the pressure reflects the difficulty of the slurry extrusion.
2. The method for testing the printability of ceramic slurry according to claim 1, characterized in that: The stress scanning range of the amplitude scanning in step (1) is 0-10000 Pa and the frequency is 1-5 Hz.
3. The method for testing the printability of ceramic slurry according to claim 1, characterized in that: The oscillation frequencies of the first oscillation test and the third oscillation test in step (2) are both 1-5 Hz, and the oscillation time is 30-300 s; the frequency of the rotation test in step (2) is 1-5 Hz, the time is 30-60 s, and the shear rate range is 50-150 s -1 .
4. The method for testing the printability of ceramic slurry according to claim 1, characterized in that: In the test of the shear properties and structural recovery properties of the ceramic slurry described in step (2), the ceramic slurry having a storage modulus value between 2300-6000 Pa and a storage modulus value of the third section that can be restored to a level equivalent to the storage modulus value of the first section has good printability.
5. The method for testing the printability of ceramic slurry according to claim 1, characterized in that: In the capillary extrusion test described in step (3), when there is an obvious peak in the extrusion pressure and extrusion displacement curve during the ceramic slurry extrusion process, and the extrusion pressure does not increase significantly with the increase of displacement, it indicates that the ceramic slurry has good printability.
Citation Information
Patent Citations
Method for measuring printing performance of liquid system three-dimensional printer system
CN101439584A
3D printed building mortar bulk property testing device
CN106568926A